2004
DOI: 10.1007/s00122-004-1807-5
|View full text |Cite
|
Sign up to set email alerts
|

Leaf-rust resistance in rye (Secale cereale L.). 2. Genetic analysis and mapping of resistance genes Pr3, Pr4, and Pr5

Abstract: Three dominant resistance genes, Pr3, Pr4, and Pr5, were identified by genetic analysis of resistance to leaf rust in rye (Puccinia recondita f. sp. secalis). Each of the three genes confers resistance to a broad scale of single-pustule isolates (SPIs), but differences could be observed for specific Pr gene/SPI combinations. Resistance conferred by the three genes was effective in both detached-leaf tests carried out on seedlings and in field tests of adult plants. Molecular marker analysis mapped Pr3 to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 29 publications
1
38
0
Order By: Relevance
“…Differentials within each of these subgroups most likely have the same resistance gene(s). This could be demonstrated for the differentials S4084 and H54/9 that carry most probably the same resistance locus on chromosome 1RS revealed by genetic mapping (Wehling et al 2003;Roux et al 2004;Klocke 2004 (Klocke 2004). Assuming that the differentials clustering closely together also have the same resistance gene(s), the differential set could be reduced to 17.…”
Section: Differential Setmentioning
confidence: 91%
See 1 more Smart Citation
“…Differentials within each of these subgroups most likely have the same resistance gene(s). This could be demonstrated for the differentials S4084 and H54/9 that carry most probably the same resistance locus on chromosome 1RS revealed by genetic mapping (Wehling et al 2003;Roux et al 2004;Klocke 2004 (Klocke 2004). Assuming that the differentials clustering closely together also have the same resistance gene(s), the differential set could be reduced to 17.…”
Section: Differential Setmentioning
confidence: 91%
“…A genetic study showed that most of the breeders' lines selected for leaf-rust resistance contained race-specific resistances (Miedaner et al 2002). Genetic analysis of racespecific resistance genes in the pathosystem rye/leaf rust is still in its infancy, leading to five chromosomally located and characterized genes from breeders' material only (Wehling et al 2003, Roux et al 2004, Klocke 2004) that were, however, not known at the beginning of this study in 2000. The long-term success of using monogenic, racespecific resistances depends on the structure and dynamics of the leaf rust populations.…”
Section: Introductionmentioning
confidence: 94%
“…Wehling et al (2003) identified in rye two dominant genes, Pr1 and Pr2 , both conferring resistance through hypersensitivity, which were recognized as active against a local population of P. recondita as well as isolates of the fungus obtained from single pustules and representing various virulence. Three additional genes, Pr3 , Pr4 , Pr5 , associated with race-specific resistance to brown rust, were identified by Roux et al (2004). Specific resistance is an effective strategy, often used in breeding, against P. recondita as well as other biotrophic pathogens, but unfortunately its durability is not satisfactory (Miedaner et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Available estimates indicated 11 to 27% thousand kernel weight reduction (Miedaner and Sperling 1995) and yield decrease of up to 80% (Solodukhina 1997 2002) depending on genotype. Modern rye varieties do not always exhibit a satisfactory level of resistance to brown rust (Solodukhina 1997; Miedaner et al 2002; Roux et al 2004). This problem, in particular, concerns the population varieties which dominate in Poland.…”
Section: Introductionmentioning
confidence: 99%
“…ventricosa (a source of resistance to eyespot) (Burt and Nicholson 2011), Ae. umbellulata (leaf rust resistance) (Sears 1956), Secale (S.) cereale (yield advantage and several genes for disease resistance) (Roux et al 2004), and Thinopyrum (Th.) bessarabicum (highly salt tolerant) (King et al 1997).…”
Section: Introductionmentioning
confidence: 99%